CENTRAL BANK DYNAMICS: A COMPARATIVE STUDY OF CONVENTIONAL MEASURES IN THE WAKE OF GLOBAL ECONOMIC UPHEAVAL - Aryoubi, Abdullah Johann; Fischer , Eva Charlotte; Schneider , Markus Heinrich (Economics and Statistics Research Journal (ESRJ), 2024)
The 2007 subprime crisis, originating in the United States, sent shockwaves across the global economy, transforming into a fullfledged financial crisis with widespread ramifications on the real economy, affecting industrialized nations worldwide. The European Union, in particular, faced significant challenges, marked by substantial write-downs on securities and loans, coupled with an estimated six percent decline in GDP (Dell'Ariccia et al., 2018). In response to shrinking economic performance, jurisdictions typically turn to monetary stimulus through their central banks, employing interest targeting instruments linked to key interest rate reductions. This paper delves into the aftermath of the 2007 subprime crisis and the subsequent financial turmoil, with a specific focus on the conventional measures adopted by central banks globally. A central tenet of these measures involves interest rate reductions, wherein commercial banks borrow capital at lowered rates from the central bank and subsequently lend these funds to both consumers and corporations. The objective is to foster favorable financing conditions, thereby stimulating investment and consumption, essential components for economic recovery. Given the widespread adoption of similar instruments by central banks worldwide, primarily revolving around key interest rates and the credit channel, these policy measures are commonly categorized as conventional measures (Mishkin, 1996). This paper critically examines the effectiveness and nuances of these conventional measures in mitigating the economic fallout following the 2007 subprime crisis. Furthermore, it investigates the variations in the implementation and outcomes of these measures across different jurisdictions, considering the unique economic landscapes and policy frameworks in place. Through a comprehensive analysis of the post-2007 subprime crisis era, this paper contributes to the existing literature on monetary policy responses to financial crises. It sheds light on the intricacies of conventional measures, exploring their limitations, successes, and potential areas for improvement. The findings of this study are crucial for policymakers, central banks, and researchers seeking to enhance the understanding of the long-term implications of conventional monetary measures in the wake of a global financial crisis.